Is the recent surge in violence in American cities due to contagion?. (September 2021) - Brantingham, P. Jeffrey; Carter, Jeremy; MacDonald, John; Melde, Chris; Mohler, George
Abstract: Firearm violence rates have increased in U.S. cities in 2020 and into 2021. We investigate contagious and non-contagious space-time clustering in shooting events in four U.S. cities (Chicago, Los Angeles, New York and Philadelphia) from 2016 to 2020. We estimate the dynamic reproduction number ( Rt ) of shootings, a measure of contagion, using a Hawkes point process. We also measure concentration over time using a spatial Gini index. We find that the contagious spread of violence increased in 2020 in several, but not all, of the cities we considered. In all four cities, non-contagious (Poisson) events comprised the majority of shootings across time (including 2020). We also find that the spatial location and concentration of shooting hot spots remained stable across all years. We discuss the implications of our findings and directions for future research. Highlights: The contagious spread of violence increased in 2020, though spontaneous events characterized most shootings. The spatial location of shooting hotspots remained stable.